Research progress of acupoint application in the treatment of constipation in patients with diabetes mellitus (穴位贴敷治疗糖尿病便秘的研究进展) - LIU Bianyuan (刘变云); GUAN Yi (关漪); ZHANG Jingjin (张京津) (中西医结合护理)
Constipation is an early and frequent neuropathic complaint among patients with diabetic mellitus. With the extensive application of Traditional Chinese medicine nursing technology in clinical treatment of common diseases, acupoint application has also achieved significant results in the clinical treatment of diabetes constipation. This article reviews the application status of acupoint application in the treatment of constipation in patients with diabetes mellitus, including operation methods, influencing factors, and effect evaluation, with a view to providing a reference for the extensive clinical practice. (便秘是糖尿病患者神经病变常见的早期症状, 严重影响患者的生活质量。随着中医护理技术在常见疾病领域的广泛开展和应用, 穴位贴敷治疗糖尿病便秘在临床也取得了良好的效果。本研究从穴位贴敷治疗糖尿病便秘的机制、效果评价方法等方面进行总结, 旨在为糖尿病便秘的中西医结合治疗提供参考。)